O uso de artigos midiáticos de divulgação científica em um Projeto Didático de Gênero: uma proposta para construção do aprendizado interdisciplinar em sala de aula - Rabello, Keli Rodrigues (Universidade do Vale do Rio dos Sinos, 2015)
The need for the continued development of teaching methods of mother tongue able to transform students' language practices and promote interdisciplinary relations of knowledge, according to advocating official documents as the PCNs and OCEM, are so Overall, the social context in which originate the motivations for developing this research. Thus, the central focus of the investigative action of this research is on didactization process of a text genre (whose social practice fosters interdisciplinary) that occurs in this research using a teaching device called Genre Didactical Projects (henceforth GDP) that enables the language of instruction through text genres, developing the students' language skills. However, demand for interdisciplinarity leads to text genre study ‘Media Articles of Science Communication'. This work presents the application of a GDP focusing on gender Article MDC in order to develop students' language skills and to foster interdisciplinary learning. The main theoretical contributions that sustain the actions of this research are located in Socio-Discursive Interacionism studies (SDI) of Bronckart (2009; 2012; 2013), in addition to studies on language skills, conducted by Dolz and Schneuwly (2011) and Cristóvão; Stutz (2011; 2013), on Teaching sequences, also Dolz and Schneuwly (2011); on literacy projects, Kleiman (1995; 1999; 2000; 2007; 2008) and the scientific and media disclosure from Charaudeau (2008; 2009; 2010). The methodological process by which it accomplishes this research consists in action research and consists of actions ranging from planning the GDP and its application in the classroom to the development of data analysis tool. The preparation of the GDP resulted in an interdisciplinary project called 'Young scientists' applied to a class of 2nd year of high school in a public school in the city of Sapucaia do Sul and with the collaboration of a Biology teacher in order to establish interdisciplinary.The data analysis indicates that the didactization of a genre as the Media Articles of Science Communication, through a language teaching device as the PDG, can indeed develop students' language skills and contribute to the construction of interdisciplinary learning in the classroom of class.
Keywords: PDG; Artigo MDC; Interdisciplinaridade; Capacidades de linguagem; Língua materna; GDP; Media articles of science comminication; Interdisciplinarity; Language skills; Mother tongue; ACCNPQ::Lingüística, Letras e Artes::Lingüística